SMART Cities, SMART Regions, SMART Solutions in Regional Innovation Ecosystems of a Selected Model Area of the South Bohemian Region - Jiri DUSEK; Stepan KAVAN (Communications of International Proceedings, 2020)
The Smart Region/City concept aims to reach sustainable growth and a balanced relationship within and between cities and the countryside, it continuously improves the quality of infrastructure and services in many areas ranging from energy industry, transport, health care, social services and education to security. The Smart concept is unique because it involves cooperation among many different fields which are different at first sight and which should be integrated into one complex whole within the Smart Region or Smart City concept. The goal of this analysis is to map the current state and the degree to which the South Bohemian Region is involved in the Smart City/Smart Region concept, to map the level of this Smart concept implementation process and the opinion of the need for its support, and subsequently to find appropriate measures to increase the involvement in the concept. An integral part of this analysis will be to determine the development and limiting factors of the Smart City/Smart Region concept.
Keywords: Developing factors; Limiting factors; SMART City; SMART Region.